Sailing to create, art in motion - Myriam Thomas (Arts et Sciences)
Science has always been a source of inspiration for artists. In this spirit, the Tara Ocean Foundation works closely and organize exhibitions with artists to cultivate fresh perspectives on its scientific expeditions and on the Ocean itself. Through residencies aboard the Tara schooner and Tara Polar Station, artists can harness their unique vision and creativity to capture and reinterpret the richness of the Ocean, the essence of scientific exploration, and the rhythms of life at sea. The goal is to awaken public awareness of the Ocean’s beauty and essential role in our world.